Prefrontal control of attention to threat - Peers, Polly V.; Simons, Jon S.; Lawrence, Andrew D. (Frontiers in Human Neuroscience, 2013)
Attentional control refers to the regulatory processes that ensure that our actions are in accordance with our goals. Dual-system accounts view temperament as consisting of both individual variation in emotionality (e.g. trait anxiety) and variation in regulatory attentional mechanisms that act to modulate emotionality. Increasing evidence links trait variation in attentional control to clinical mood and anxiety disorder symptoms, independent of trait emotionality. Attentional biases to threat have been robustly linked to mood and anxiety disorders. However, the role of variation in attentional control in influencing such biases, and the neural underpinnings of trait variation in attentional control, are unknown. Here, we show, that individual differences in trait attentional control, even when accounting for trait and state anxiety, are related to the magnitude of an attentional blink following threat-related targets. Moreover, we demonstrate that activity in dorsolateral prefrontal cortex, is observed specifically in relation to control of attention over threatening stimuli, in line with neural theories of attentional control, such as guided activation theory. These results have key implications for neurocognitive theories of attentional bias and emotional resilience.